2020
DOI: 10.21203/rs.3.rs-62592/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emerging of a SARS-CoV-2 viral strain with a deletion in nsp1

Abstract: Background:The new Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), which was first detected in Wuhan (China) in December of 2019 is responsible for the current global pandemic.Phylogenetic analysis revealed that it is similar to other betacoronaviruses, such as SARS-CoV and Middle-Eastern Respiratory Syndrome, MERS-CoV. Its genome is ∼30 kb in length and contains two large overlapping polyproteins, ORF1a and ORF1ab that encode for several structural and non-structural proteins. The non-structural … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Although we found that genes coding for ribosomal proteins (RPS/RPL) and pathways related to mRNA/protein metabolism were differentially regulated in mutant Nsp1-expressing cells compared to the WT Nsp1, it remains to be examined how the deletion, particularly the key residues in the N-terminal domain affects host cell translation or mRNA decay. Interestingly, several other Nsp1 mutants were also identified in different geographical areas (Benedetti et al, 2020;Islam et al, 2020). These results indicate that SARS-CoV-2 is undergoing profound genomic changes and evolution and that Nsp1 is likely important for viral phenotypes.…”
Section: Discussionmentioning
confidence: 78%
“…Although we found that genes coding for ribosomal proteins (RPS/RPL) and pathways related to mRNA/protein metabolism were differentially regulated in mutant Nsp1-expressing cells compared to the WT Nsp1, it remains to be examined how the deletion, particularly the key residues in the N-terminal domain affects host cell translation or mRNA decay. Interestingly, several other Nsp1 mutants were also identified in different geographical areas (Benedetti et al, 2020;Islam et al, 2020). These results indicate that SARS-CoV-2 is undergoing profound genomic changes and evolution and that Nsp1 is likely important for viral phenotypes.…”
Section: Discussionmentioning
confidence: 78%
“…Among the SARS-CoV-2 non-structural protein variants, deletion at position Asp268 of NSP2 spread rapidly in Europe [81]. Deletion of three amino acids, KSF towards the 3′ end of NSP1 at positions 241–243 was found in viral isolates from different geographical locations, suggesting their rapid spread [82]. Whether such mutations have any effect on viral pathogenicity needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…The role of NSP1 is to dampen the immune responses through host shut-off by inhibiting host ribosomal translation [162]. This deletion is hypothesised to destabilise the C-terminal domain, potentially impacting viral replication and leading to a less pathogenic phenotype [163]. Furthermore, a single amino acid deletion in NSP1 (Δ85) has been described in several variants of concern-like viruses or immunocompromised patient sequences (Tables 1 and 2) [61,115].…”
Section: Other Rarer Deletions Of Attenuating or Unknown Phenotypementioning
confidence: 99%